COVID-19, LEARNING & DIVIDENDS - Adehi, Mary . U; Maijamaa, Bilkisu (African Journal of Education and Practice, 2020)
The era of coronavirus pandemic (November 2019 to June 2020) has been a traumatic period for all countries around the globe. It was a very sober period because the virus is a novel one, and mortality and infection rates were on very rapid increase while scientists battled with treatment measures as well as vaccine discoveries to quell the pandemonium. The home front and life style in general changed, while the big question is, was there a benefit? People generally embraced virtual meetings to be able to interact and move on with life. The 16 Plus school in Lagos Nigeria was not left out of these meetings, as such, during one of such virtual meetings for the end of semester assembly, 30th May, 2020, we presented this paper to 65 members of staff, 10 parents and 25 graduating students (age 16 and above) with an objective to identify some benefits of the pandemic period. Some methods that were adopted to extract information for this paper include google search of periodicals. It is really nice to note that despite all odds, "˜lemonades were made from lemons' in covid-19 era.